Complete chloroplast genome and phylogenetic analysis of Lonicera caerulea var. edulis (Caprifoliaceae) - Chenqiao Zhu; Xinyu Sun; Qiang Fu; Ying Zhan; Songlin Li; Yu Liu; Min Yu; Dong Qin; Lijun Zhang; Junwei Huo (Mitochondrial DNA. Part B. Resources, 2023)
Lonicera caerulea var. edulis, known as “blue honeysuckle” or “Haskap,” is a deciduous shrub that belongs to the Caprifoliaceae family. Characterized by the high cold hardiness and high quality of fruit, it has become a novel cash crop in cold regions worldwide. The lack of available chloroplast (cp) genome information limits studies of its molecular breeding and phylogeny. Here, the complete cp genome of Lonicera caerulea var. edulis was assembled and characterized for the first time. It was 155,142 bp in length with 38.43% of GC content, including 23,841 bp inverted repeat regions (IRs), an 88,737 bp large single-copy region (LSC), and an 18,723 bp small single-copy region (SSC). A total of 132 genes, including 85 protein-coding genes, 8 rRNA genes, and 39 tRNA genes were annotated. Phylogenetic analysis indicated that L. caerulea var. edulis was closely related to L. tangutica. These data and results provide a valuable resource for the development of breeding tools and genetic diversity studies for L. caerulea.